Litterfall and Element Fluxes in a Natural Hardwood Forest and a Chinese‐fir Plantation Experiencing Frequent Typhoon Disturbance in Central Taiwan. (22nd June 2013) - Wang, Hsueh‐Ching; Wang, Su‐Fen; Lin, Kuo‐Chuan; Lee Shaner, Pei‐Jen; Lin, Teng‐Chiu
Abstract: Chinese fir ( Cunninghamia lanceolata ) is the most important forest plantation species in subtropical Asia and is rapidly replacing natural forests. Such land‐use change may affect ecosystem nutrient cycling through changes in litterfall nutrient flux. Tropical cyclones often cause pulses of litterfall. Previous studies, however, have mostly focused on the effects of a single cyclone with little effort examining the effects of repeated cyclones. We examined litterfall in a natural hardwood forest and a Chinese‐fir plantation in central Taiwan experiencing an average of one typhoon per year. The natural hardwood forest had 54 percent higher annual litterfall (11, 400 kg/ha/yr) than the Chinese‐fir plantation (7400 kg/ha/yr). Four typhoon‐affected months (typhoon period) contributed to approximately 60 percent of the litterfall and litterfall element flux in the natural hardwood forest and 80 percent in the Chinese‐fir plantation, with contributions from individual typhoons varied by more than twofold. Litterfall N and P concentrations were significantly higher in typhoon period than in non‐typhoon period, likely the result of limited retranslocation. Precipitation was a better predictor of quantity of typhoon‐associated litterfall than wind velocity. Both types of forests in southeastern China beyond the reach of typhoons have litterfall peaks in the dry season. In contrast, we measured higher litterfall during the typhoon period than during the dry season, suggesting that in regions with frequent cyclones, cyclones drive temporal variation of litterfall. Global climate change is affecting the frequency and intensity of cyclones; therefore, knowledge of typhoon‐litterfall dynamics is indispensable for understanding the effects of climate change on ecosystem nutrient cycling.